Posterior Segment Intraocular Foreign Body: Extraction Surgical Techniques, Timing, and Indications for Vitrectomy - Dante A. Guevara-Villarreal; Patricio J. Rodríguez-Valdés (Journal of Ophthalmology)
Ocular penetrating injury with Intraocular Foreign Body (IOFB) is a common form of ocular injury. Several techniques to remove IOFB have been reported by different authors. The aim of this publication is to review different timing and surgical techniques related to the extraction of IOFB. Material and Methods. A PubMed search on “Extraction of Intraocular Foreign Body,” “Timing for Surgery Intraocular Foreign Body,” and “Surgical Technique Intraocular Foreign Body” was made. Results. Potential advantages of immediate and delayed IOFB removal have been reported with different results. Several techniques to remove IOFB have been reported by different authors with good results. Conclusion. The most important factor at the time to perform IOFB extraction is the experience of the surgeon.